A generic brain trauma computer framework to assess brain injury severity and bridging vein rupture in traumatic falls - Bastien, C .; Sturgess, C. Neal; Davies, H.; Hardwicke, J.; Cloake, T .; Zioupos, Peter (Juniper Publishers, 2021)
Traumatic Brain Injuries (TBI) have been a major cause of morbidity and mortality for many years. The Organ Trauma Model (OTM) is a state of the art computer model, available to scientific community, which can calculate the threat to the life via white and grey matter brain injury severity level based on Peak Virtual Power (PVP), founded on the 2nd law of thermodynamics. The OTM model has however assumed, based on previous literature, that bridging veins rupture when the grey matter maximum principal strain exceeds 25.5%. This assumption does not permit to locate the vein tear as well as quantify the blood loss, which defines the injury severity. A 10-pair bridging vein shell computer model was devised, using published material properties and geometrical data connecting the grey matter to the dura, and defined a maximum principal strain to rupture of 15%. This bridging vein model was then tested in the case of a fall and correctly predicted the location of tear, as well as how many veins were damaged, suggesting that it is possible, with more validation cases, to link the number of damaged veins to the AIS level. This bridging vein model is a novel concept model which is showing a plausible response in direct linear impact and could be a good candidate for EuroNCAP pedestrian head strike against the vehicle, as well as helmet safety performance assessment. It has however not yet been validated in angular acceleration motions, hence more testing will be required in due course.
Keywords: Traumatic brain injuries; Organ trauma model; THUMS; Bridging veins; Peak virtual power